Effectiveness and risks of dapagliflozin in treatment for metabolic dysfunction-associated steatotic liver disease with type 2 diabetes: a randomized controlled trial - Fukada, Hiroo; Kon, Kazuyoshi; Yaginuma, Reiko; Uchiyama, Akira; Morinaga, Maki; Ishizuka, Kei; Fukuhara, Kyoko; Okubo, Hironao; Suzuki, Satoko; Nojiri, Shuko; Yamashina, Shunhei; Ikejima, Kenichi (Frontiers in Medicine, 2025)
IntroductionPharmacotherapy for metabolic dysfunction-associated steatotic liver disease (MASLD) is still under development and has not been fully established. For patients with MASLD and type 2 diabetes, treatment with antidiabetic drugs, including sodium–glucose cotransporter 2 (SGLT2) inhibitors, is recommended, with vitamin E supplementation when treatment efficacy is insufficient. The benefits and risks of SGLT2 inhibitors for MASLD with type 2 diabetes have not been thoroughly investigated.ObjectiveThis prospective randomized controlled trial aimed to elucidate the effectiveness and risks of the SGLT2 inhibitor dapagliflozin in comparison with vitamin E in patients with MASLD and comorbid type 2 diabetes.MethodsThe trial enrolled 24 patients with MASLD and comorbid type 2 diabetes, who were assigned to receive either dapagliflozin (5 mg/day) or vitamin E (150 mg/day) for 24 weeks. The primary outcomes included serum levels of AST, ALT, γ-GT, and type IV collagen, and the FIB-4 index. The secondary outcomes were BMI, HbA1c and serum ferritin levels, lipid profile, body composition assessed using InBody, and hepatic fat content and fibrosis evaluated with FibroScan. Adverse events were monitored throughout the study period.ResultsBoth groups demonstrated significant reductions in serum AST and ALT levels but intergroup differences were not significant. The dapagliflozin group showed additional benefits, with significant decreases in BMI and HbA1c, γ-GT, ferritin, LDL cholesterol, and body fat levels, indicating improved glycemic control and lipid profile. Dapagliflozin administration was associated with a significant decline in the skeletal muscle index, indicating a risk of muscle loss absent in the vitamin E group. This reduction in muscle mass is clinically significant as it suggests a potential risk of worsened overall survival with dapagliflozin treatment.ConclusionThis study indicates that dapagliflozin provides several metabolic benefits in patients with MASLD and comorbid type 2 diabetes, including reductions in the levels of liver enzymes and body fat, but the observed decrease in muscle mass suggests a potential adverse effect on long-term survival outcomes. Muscle mass should be monitored in patients receiving dapagliflozin therapy to mitigate the risk of sarcopenia progression and ensure a comprehensive approach to MASLD management.Clinical trial registrationhttps://jrct.niph.go.jp/re/reports/detail/81182, identifier jRCT1031180386.